Picomolar Sensitivity Analysis of Multiple Bradykinin-Related Peptides in the Blood Plasma of Patients With Hereditary Angioedema in Remission: A Pilot Study - Marceau, François; Rivard, Georges-Etienne; Hébert, Jacques; Gauthier, Julie; Bachelard, Hélène; Gangnus, Tanja; Burckhardt, Bjoern B. (Frontiers in Allergy, 2022)
Background Hereditary angioedema (HAE) is a rare autosomal dominant disease; the most well understood forms concern the haplodeficiency of C1 esterase inhibitor (C1INH) and a gain of function mutation of factor XII (FXII). The acute forms of these conditions are mediated by an excessive bradykinin (BK) formation by plasma kallikrein. Methods A validated LC-MS/MS platform of picomolar sensitivity developed for the analysis of eleven bradykinin-related peptides was applied to the plasma of HAE-C1INH and HAE-FXII sampled during remission. Results In HAE-C1INH plasma, the concentrations of the relatively stable BK1−5 fragment (mean ± S.E.M.: 12.0 ± 4.2 pmol/L), of BK2−9 (0.7 ± 0.2 pmol/L) and of the sums of BK and its tested fragments (18.0 ± 6.4 pmol/L) are significantly greater than those recorded in the plasma of healthy volunteers (1.9 ± 0.6, 0.03 ± 0.03 and 4.3 ± 0.8 pmol/L, respectively), consistent with the previous evidence of permanent plasma kallikrein activity in this disease. Kinin levels in the plasma of HAE-FXII patients did not differ from controls, suggesting that triggering factors for contact system activation are not active during remission. Conclusion BK1−5, BK2−9 and the sum of BK and its fragments determined by the sensitive LC-MS/MS technique are proposed as potential biomarkers of HAE-C1INH in remission while this was not applicable to HAE-FXII patients.